EFFECTIVENESS OF BEHAVIORAL FINANCE IN PERSONAL INVESTMENT DECISIONS (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
Behavioral finance explores how psychological factors influence financial decision-making, diverging from traditional economic theories based on rationality. This abstract examines the effectiveness of behavioral finance in personal investment decisions. It reviews research indicating that human biases, emotions, and cognitive errors significantly impact investment choices, often leading to suboptimal outcomes.Studies suggest that awareness of behavioral biases, such as loss aversion and overconfidence, can improve decision-making by prompting investors to adopt more balanced and informed strategies. Behavioral finance frameworks, such as prospect theory and behavioral biases, provide valuable insights into understanding investor behavior and improving financial outcomes.This abstract highlights the importance of integrating behavioral finance principles into investment practices to mitigate biases and enhance decision-making quality. By acknowledging the psychological aspects of investing, individuals can make more rational and disciplined choices aligned with their financial goals and risk tolerance. This study contributes to the growing body of literature supporting behavioral finance as a beneficial approach for guiding personal investment decisions.